Pyridostigmine induced heart block requiring ICU admission. Issue 5 (3rd September 2018) - Chaucer, Benjamin; Whelan, Dustin; Lamichhane, Dronacharya
ABSTRACT: Myasthenia gravis is an autoimmune disorder that effects an estimated 20 people per 100, 000 in the USA per year. Pyridostigmine is a common drug used in the symptomatic treatment of myasthenia gravis. While generally safe and effective, a rare set of patients treated with pyridostigmine encounter cardiac conduction disorders. Here, we report a rare presentation of an adverse drug reaction due to pyridostigmine, which is important for its implications in the acute care setting.